A study of two-phase flow in monoliths using ultrafast single-slice X-ray computed tomography. (November 2016) - Schäfer, Thomas; Meitzner, Christine; Lange, Rüdiger; Hampel, Uwe
Highlights: Ultrafast single-slice X-ray computed tomography has been applied. Cross-sectional liquid holdup inside the monolith has been visualized and quantified. Gas-liquid maldistributions have been evaluated for different feeding conditions. Longitudinal sectional liquid holdup distributions have been calculated. Characteristic spatial and temporal holdup pattern inside the monolith channels patterns could be identified and, associated with the flow regime. The in-channel flooding and draining behavior has been investigated. Abstract: Running chemical reactions in monolithic structures is being considered as highly promising for intensifying industrial reaction processes. A potential pitfall of such structures is the difficulty to achieve homogeneous and well defined gas/liquid distributions patterns with economically feasible distribution mechanisms. Experimental studies on gas/liquid distribution in monoliths are often hampered by missing measurement and visualization techniques to disclose the two-phase flow inside the narrow and opaque channels. This paper presents results of a study carried out with ultrafast single-slice X-ray tomography, a novel imaging technique, which can overcome these limitations. We investigated two-phase flow in two different types of square-channel monolith structures, one with high cell density of 400 cpsi and one with low cell density of 39 cpsi. Our study discloses in-channel flooding and draining behavior via extraction of characteristic distribution parameters, such as averaged and channel-linked liquid holdup, two-phase flow patterns and liquid maldistribution from X-ray images using advanced image processing techniques.